Avaliação de erva-mate para chimarrão (Ilex paraguariensis St. Hil.) por métodos instrumentais e quimiometria - Vieira, Tatiane Francielli (2018)
The cultivation practices and harvesting and post-harvest steps of yerba mate are conducted by different methods depending on the region, factors that, as well as types of herbs (native or reforested) and genetic and environmental variability, influence in their quality and final chemical composition. In this way, it is considered important to verify its authenticity, which requires the use of fast, efficient and reliable analytical methods. Thus, the objective of the study was to evaluate yerba mate samples for chimarrão, acquired from the Paraná, Santa Catarina and Rio Grande do Sul states, in order to discriminate them regarding the sugar content and the geographic origin, exploring rapid instrumental methods combined with chemometric analyzes. For this, colorimetry, electronic nose, visible and near infrared spectroscopy (NIR) techniques were used in conjunction with chemometrics exploratory and classification methods. In addition, composition data obtained by High Performance Liquid Chromatography (HPLC) and data of phytochemical compounds and antioxidant activity in vitro, collected in a previous work, were also used. In the multiblock exploratory analysis (ComDim) five common dimensions were required to represent 97% of the variance contained in the tables evaluated. The colorimetry and visible spectroscopy analyzes indicated that possibly the yerba mate samples obtained from Santa Catarina and Rio Grande do Sul consist of mixtures with the yerba mate produced in Paraná. The analysis of volatile organic compounds by electronic nose evidenced that the samples of Paraná were shown to be richer in the volatile compounds detectable by the sensors. The ComDim multiblock analysis was able to discriminate samples containing sugar in the second common dimension, which presents a high contribution of the NIR spectra. However, ComDim did not discriminate the samples geographically, which may have resulted from a possible mixture of different states herbs. From the results obtained by the ComDim it was observed that the NIR spectra presented the best discrimination capacity of the samples. Thus, PLS-DA models were developed to classify herbs mate how much the presence of sugar and geographical origin. The PLS-DA also assertively classified the samples in relation to the presence of sugar with sensitivity and specificity equal to 100%. PLS-DA was able to discriminate partially the samples by geographic origin with mean values of 76.67% for sensitivity and 80.84% for specificity. However, the NIR spectra provided a better classification compared to the models obtained for chemical composition data for classification by geographic origin, which presented average sensitivity and specificity equal to 57.78% and 88.81%, respectively. The employment of rapid techniques, especially the nearinfrared spectroscopy, combined with the chemometric methods allowed the discrimination of the yerba mate samples, especially by presence sugar, and for this purpose, presented advantages over HPLC techniques and analysis of phytochemical compounds and antioxidant activity in vitro, for being faster, nondestructive and does not generate chemical residues.